Systematic Review: CD4 Increase in HIV/AIDS Patients - Arif Imam Hidayat (International Journal of Biomedical Nursing Review, 2023)
Introduction: Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms and infectious diseases caused by damage to the human immune system due to infection with the HIV (Human Immunodeficiency Virus). The type of CD4 T lymphocyte cell is the main target of the HIV virus in infecting the human body. The lower the number of CD4 T lymphocytes in the blood, the lower a person's immune system will be. Methods: The authors conducted an article search beginning on June 10 using research in an electronic database. The Identified Article is a research study that investigates CD4 cell elevation in HIV/AIDS patients. Systematic compilation begins with search databases on Google Scholar, PHPJ, PubMed. the method is based on a prismatic systematic guideline and is systematically reviewed. Discussion: The results of this study indicate that the more progressive the HIV infection in a person's body, the lower his CD4 level will be. A decrease in CD4 levels will be followed by a decrease in the number of lymphocytes, the ratio of lymphocytes to leukocytes, and the ratio of lymphocytes to neutrophils. This shows that the immune system of people infected with HIV is decreasing. Conclusion: The more severe the condition of people with HIV infection, the lower the CD4 count. Complete blood counts were performed automatically using Abbott Diagnostics' CELL-DYN Ruby Hematology Analyzer.